2021
DOI: 10.3389/fendo.2021.763846
|View full text |Cite
|
Sign up to set email alerts
|

Cross Talk Between Macrophages and Cancer Cells in the Bone Metastatic Environment

Abstract: The skeleton is a common site for cancer metastases with the bone microenvironment providing the appropriate conditions for cancer cell colonization. Once in bone, cancer cells effectively manipulate their microenvironment to support their growth and survival. Despite previous efforts to improve treatment modalities, skeletal metastases remain with poor prognoses. This warrants an improved understanding of the mechanisms leading to bone metastasis that will aid development of effective treatments. Macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 275 publications
(329 reference statements)
0
7
0
Order By: Relevance
“…Aberrant efferocytosis is associated with numerous inflammatory diseases, autoimmune disorders and cancers [ 46 48 ]. Among pertinent examples, failure to clear apoptotic bodies drives lesion progression and plaque stability in atherosclerosis [ 49 , 50 ] and in metastatic bone disease, macrophage efferocytosis of apoptotic cancer cells creates a microenvironment that promotes tumor progression [ 47 , 48 ]. The iCasp9 mice can facilitate further investigation into these pathologies focused at elucidating the phenotypes of defective efferocytosis that will inform the development of corrective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant efferocytosis is associated with numerous inflammatory diseases, autoimmune disorders and cancers [ 46 48 ]. Among pertinent examples, failure to clear apoptotic bodies drives lesion progression and plaque stability in atherosclerosis [ 49 , 50 ] and in metastatic bone disease, macrophage efferocytosis of apoptotic cancer cells creates a microenvironment that promotes tumor progression [ 47 , 48 ]. The iCasp9 mice can facilitate further investigation into these pathologies focused at elucidating the phenotypes of defective efferocytosis that will inform the development of corrective strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that KIFC1 may play a part in regulating the polarization of TAM. Researchers have found that TAM can promote tumor cells’ growth and metastasis through a variety of pathways ( Batoon and McCauley, 2021 ; Kong et al, 2021 ). This could partly explain why KIFC1 can promote LIHC progress.…”
Section: Discussionmentioning
confidence: 99%
“…In a PyMT mouse model, the expression of RANK in luminal BC led to the recruitment of TAMs and TANs, which inhibited T lymphocyte recruitment and/or activity [ 56 ]. CCL2 and CXCL12 are well-known key signaling pathways in BC bone metastases [ 57 , 58 ].…”
Section: The Cells Of Innate Immunity and Their Role According To The...mentioning
confidence: 99%